La motricidad fina en la coordinación óculo-manual en los niños de Subnivel Inicial 2 de la Unidad Educativa Simón Rodríguez, Cantón Riobamba - Tiuquinga Farinango, Katherine Daniela (2024)
The present research work entitled “Fine Motor Skills in eye-hand coordination in children of preschool Sublevel 2 at Simón Rodríguez Elementary School of Riobamba Canton” was developed with the aim of determining the impact of the fine motor skills on eye hand- coordination in this group of preschoolers. The theoretical foundation is bases on its two study variables: fine motor skills and eye hand-coordination, to obtain the appropriate information and a descriptive depth. In addition, it has a mixed approach; not manipulating its variables, its employs a non-experimental design. Due to its time factor, it is transversal, having been conducted within a specific timeframe, and it is descriptive, bibliographic, and field-based. The research was applied to a total of 34 children from the Educational Institution, and several activities were proposed to address this issue, favoring the strengthening of eye hand-coordination. As son as the activities were applied using the instrument simultaneously, the results were subsequently analyzed and interpreted. It was concluded that fine motor skills do have an impact on the eye hand-coordination of the students, and it is very important to stimulate it from an early age with dynamic activities to strengthen motor skills and abilities that are useful for perfoming tasks both inside and outside the classroom. Moreover, it aids in the enhancement of eye hand coordination and fine motor development, ensuring that their learning reaches the required levels for the beginning of the Reading and writing process.